Learning from organization: formative practices of children in a social organzation (Praxis Educativa, 2016)
The social and political organization Teresa Israel carries out an educational project with children, called AulaVereda (AV), in Buenos Aires city, where they develop school support and recreational activities. Based on the idea of children as active and reflexive in their pedagogical processes, we propose to analyze the concepts that the children have marked as relevant in AV, and establish the ways in which they choose certain contents and ignore others from the variety that circulates in the place. In order to reach this aim, an ethnographic work was executed built on the participant observation and a hermeneutic approach that was applied together with the use of photographs, drawings, videos and interviews to capture what the children themselves signify in their own learning processes
Keywords: childhood; learning; political organization; appropriation; ethnography